THE ROLE OF INDOOR GAMES IN ENHANCEMENT OF MENTAL HEALTH - Reddy, A.Sankar (The journal of contemporary issues in business and government, 2007)
Mental health is a complex phenomenon depends on a set of familiarly personal, psychological and social variables. Mental health is an important feature as the physical health of a person to make him complex with balance mental disposition of the children to cope with life more effectively and productively.